Nanoparticle assembly: a perspective and some unanswered questions - Kumar, Sanat K.; Kumaraswamy, Guruswamy; Prasad, Bhagavatula L. V.; Bandyopadhyaya, Rajdip; Granick, Steve; Gang, Oleg; Manoharan, Vinothan N.; Frenkel, Daan; Kotov, Nicholas A. (Current Science, 2017)
In early 2016, the Royal Society of Chemistry arranged a meeting on the topic 'Nanoparticle Assemblies: from Fundamentals to Applications' which was hosted at IIT-Bombay, Mumbai. The meeting brought several leading nanoscience and nanotechnology researchers to India and is only the second Faraday Discussions meeting to have been held in the country. The papers presented at the meeting and the resulting active discussions have been summarized in a Faraday Discussion issue(1). The broad range of topics discussed at the meeting led to an understanding on where we stand in the field of nanoparticle assembly, and also enunciated some of the outstanding fundamental and practical issues that remain to be resolved before these ideas can be applied to practical situations. Driven by these ideas, here we focus on four topics/questions: (i) Can we achieve function-driven design of nanoparticle assemblies? (ii) What is the minimal information needed to build a desired assembly? (iii) How complex a structure can one build? How can one make it responsive? What are the relative roles of equilibrium versus dynamics in the assembly process, and are we at a point where we can now pursue active assembly as a viable mode for creating complex assemblies? (iv) What are the applications that are being targeted and what are the barriers to implementation? In this perspective, we do not present an exhaustive survey of the vast literature in this area, but indicate overarching themes/questions that require immediate attention, largely based on the discussions at the Mumbai meeting.